Copper supported catalyst with space confinement effect for water gas shift reaction and preparation method thereof
By introducing a g-C3N4 anchoring strategy into the Cu/SBA-15 catalyst, the migration of copper nanoparticles was limited, and the problems of short catalyst life and poor stability were solved, and the catalytic activity and stability of the water-gas transformation reaction were significantly improved.
Patent Information
- Application Number
- CN202510130211.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-02-05
AI Technical Summary
The existing Cu/SiO2 catalyst has short life and poor stability, and the Cu/SBA-15 catalyst is easy to agglomerate and sinter, which seriously restricts its actual production application.
Through the g-C3N4 anchoring strategy, Cu nanoparticles are anchored on their defect positions and loaded into the mesopore of SBA-15 carrier. The migration of copper nanoparticles is restricted by physical and chemical domain constraints and the dispersion of Cu nanoparticles is improved.
High dispersion and stability of copper nanoparticles are achieved, and the catalytic activity and stability of water-gas transformation reaction are significantly improved.
Smart Images

Figure CN119733551A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst preparation and heterogeneous catalysis, and specifically relates to a copper-loaded catalyst with a confinement effect for a water-gas shift reaction and a preparation method thereof. Background Art
[0002] Hydrogen energy is clean, efficient and widely available, and is considered to be an important form of energy for achieving environmental friendliness and sustainable development in the future. Fossil fuels are an important source of hydrogen, which is mainly produced through chemical production methods such as coal gasification and natural gas reforming. There are two main processes involved, namely the gasification or reforming reaction that converts fossil fuels into carbon monoxide and the water-gas shift reaction that converts carbon monoxide into carbon dioxide and produces hydrogen. Therefore, the water-gas shift reaction (Water-Gas Shift, WGS, CO+H2O→CO2+H2, ΔH=-41.1 kJ / mol) is one of the most important catalytic processes for industrial hydrogen production. In this process, the catalyst is the key to improving the reaction efficiency and improving the economic benefits.
[0003] The WGS process is exothermic, and low temperature is beneficial to the reaction. However, the WGS reaction rate is low at low temperatures. In order to improve the efficiency of the WGS reaction, current research is mainly focused on the development of high-performance supported metal catalysts. Therefore, Cu-based catalysts with good water-gas shift reaction performance at low temperatures have been widely studied. Chinese patent CN111389399B discloses a Cu / SiO2 catalyst prepared by an ammonia evaporation-hydrothermal method, which obtains stable small-sized metal Cu nanoparticles and Cu + Species, improve the ability of the catalyst to dissociate water and adsorb CO, and show high catalytic activity in the water-gas shift reaction. Chen et al. (Chen, et al. ACSCatal. 2013, 3, 4, 667–677) reported the use of SBA-15 functionalized with carboxylic acid groups to load Cu nanoparticles. The Cu on the synthesized catalyst is highly dispersed, providing abundant active sites, effectively improving the selectivity and activity of the reaction. Chinese patent CN105107513A proposes a method for preparing a Cu-based water-gas shift catalyst using mesoporous silicon as a template. By regulating the parameters of the preparation process, the catalyst can be evenly dispersed in the pores and surface of the organic structure directing agent, while greatly improving the dispersion of the metal active components, effectively avoiding the sintering of the catalyst at high temperature; it has the characteristics of good thermal stability, high conversion activity, large specific surface area, and high dispersion of active components. Chen et al. (Chen, et al.ChemCatChem.2020, 12, 18) successfully prepared CuO by ammonia hydrothermal method. x / SiO2 precursor, Cu 0 and Cu +It is active for CO adsorption and water dissociation, especially Cu 0 and Cu + The particle size of CO is small, and the + The adsorption ratio on Cu 0 The adsorption on 0 The dissociation ratio of Cu to water + However, the Cu / SiO2 catalyst has problems such as short life and poor stability. The copper species of the Cu / SBA-15 catalyst reported in the above article is prone to agglomeration and sintering, which seriously restricts its actual production application. Summary of the invention
[0004] In view of the problems of poor life and stability of current Cu / SiO2 catalysts and easy agglomeration and sintering of Cu / SBA-15, the purpose of the present invention is to anchor Cu nanoparticles at their defect sites through a g-C3N4 anchoring strategy to form smaller Cu nanoparticles and load them into the mesopores of the SBA-15 carrier; through physical and chemical confinement, the migration of copper nanoparticles is restricted, the dispersion of Cu nanoparticles is improved, and excellent catalytic activity and stability of the water-gas shift reaction are exhibited.
[0005] To achieve the above purpose, the present invention adopts the following technical steps: A method for preparing a copper-supported catalyst with spatial confinement effect for water-gas shift reaction, comprising anchoring active component Cu nanoparticles on defect sites of graphite-like carbide (g-C3N4), and confining them in the pores of an SBA-15 carrier to obtain a supported Cu-NC / SBA-15 catalyst.
[0006] Furthermore, the loading amount of the active component Cu in the Cu-supported catalyst is 12-32 wt.%.
[0007] The preparation method of the Cu supported catalyst comprises the following steps: (1) Preparation of carrier SBA-15: The organic structure directing agent P123 was dissolved in hydrochloric acid, and then the silicon salt precursor was slowly added under vigorous stirring. The mixed solution was stirred for 24 h and then transferred into a stainless steel autoclave for hydrothermal reaction for 24 h. The product was filtered, washed, dried and calcined to finally obtain SBA-15. (2) Metal loading: The polymer and copper salt are dissolved in deionized water, and the SBA-15 carrier is added for impregnation to obtain a Cu-NC / SBA-15 wet sample, which is then dried, ground, and calcined to obtain a Cu-NC / SBA-15 catalyst precursor; (3) The Cu-NC / SBA-15 catalyst precursor obtained in step (2) is reduced to obtain a copper-supported catalyst.
[0008] Furthermore, in step (1), the usage ratio of the organic structure directing agent P123, the silicon salt precursor and the hydrochloric acid is 1 g:2 g:37.5 mL.
[0009] Furthermore, the silicon salt precursor in step (1) is tetraethyl orthosilicate.
[0010] Furthermore, the stirring and heating temperature in step (1) is 35-40°C; Furthermore, the hydrothermal temperature in step (1) is 100-150°C; Furthermore, the calcination in step (1) is carried out under static air, with the temperature being increased to 500-600°C at a rate of 4-5°C / min and maintained for 2-3 hours.
[0011] Furthermore, the copper salt in step (2) includes one or more of copper nitrate, copper carbonate, copper chloride and copper sulfate.
[0012] Furthermore, the polymer in step (2) includes one or more of melamine, urea, cyanamide, and dicyandiamide, and the mass ratio of the polymer to the carrier SBA-15 is 1:1.
[0013] Furthermore, the immersion time in step (2) is 12-24 h; Furthermore, the calcination conditions in step (2) are to increase the temperature to 500-600°C at a rate of 4°C / min under hydrogen, nitrogen and air, and maintain the temperature for 1-2 h.
[0014] Furthermore, the reduction in step (3) is carried out in an atmosphere of 5 vol.% H2 / N2 at 300-400°C for 2-4h.
[0015] A copper-supported catalyst with a spatial confinement effect for water-gas shift reaction prepared by the preparation method.
[0016] The application of the copper-supported catalyst with spatial confinement effect for water-gas shift reaction in water-gas shift reaction.
[0017] The technical solution of the present invention has the following advantages: The present invention provides a Cu-based water-gas shift catalyst with confinement effect. By selecting an organic mesoporous silicon material SBA-15 with a large specific surface area, adjustable pore size and hydrothermal stability as a carrier, and introducing g-C3N4 to provide defect sites, combined with the confinement effect of the SBA-15 mesoporous pores and the anchoring effect of the pore wall, highly dispersed copper species are assembled into the SBA-15 carrier pores to prepare small-sized, stable copper particles, exposing a large number of active edges. Among them, the carrier modified with N-doped carbon material (g-C3N4) is conducive to the dispersion of copper nanoparticles; at the same time, SBA-15 as a mesoporous molecular sieve can spatially limit the growth of copper nanoparticles, create a large number of spatially restricted micro-reaction environments, and thus improve the activity and stability of the catalyst in the water-gas shift reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The small-angle XRD spectra of the carrier SBA-15 and the catalyst precursor obtained in Example 2.
[0019] Figure 2 The XRD spectra of the commercial SiO2 carrier, the SBA-15 carrier, and the catalysts obtained in Example 2 and Comparative Examples 1-2 after being reduced at 350°C.
[0020] Figure 3 H2-TPR diagrams of the catalyst precursors obtained in Example 2 and Comparative Examples 1 and 2.
[0021] Figure 4 The activity comparison chart of the catalysts obtained in Examples 1-12 and Comparative Examples 1-2; (a) the activity of Example 2 and Comparative Examples 1-2; (b) the activity of Examples 1, 2, 8-10; (c) the activity of Examples 2, 11 and 12; (d) the activity of Example 2-7.
[0022] Figure 5 The stability diagram of the catalysts obtained in Example 2 and Comparative Examples 1-2.
[0023] Figure 6 TEM images of the catalysts obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION
[0024] A Cu-based catalyst with confinement effect for water-gas shift reaction, the preparation method of which comprises the following steps: (1) Preparation of carrier SBA-15: The mixture of organic structure directing agent and hydrochloric acid was heated at 38 °C and stirred continuously until the organic structure directing agent was completely dissolved, and then the silicon salt precursor was slowly added under vigorous stirring, and the mixed solution was stirred at this temperature for 24 h, and then transferred to a stainless steel autoclave and hydrothermal at 100 °C for 24 h. After filtration, washing, and drying, the temperature was raised to 600 °C at a rate of 4-5 °C / min in a static atmosphere and kept for 2 h to finally obtain SBA-15; the ratio of the organic structure directing agent P123, silicon salt precursor and hydrochloric acid used was 1 g:2 g:37.5 mL; (2) Metal loading: The polymer and copper salt are dissolved in deionized water by conventional impregnation method, and the SBA-15 carrier prepared in step (1) is impregnated with the mixed solution for 24 h to obtain a Cu-NC / SBA-15 wet sample. Then, after drying and grinding, the sample is heated to 500-600 °C at a rate of 4 °C / min in an atmosphere and calcined for 1-2 h to obtain a Cu-NC / SBA-15 catalyst precursor. (3) The Cu-NC / SBA-15 precursor obtained in step (2) is reduced in a 5 vol.% H2 / N2 atmosphere at 300-400°C for 2-4 h to obtain a copper-supported catalyst, wherein the proportion of Cu in the catalyst is 12-32 wt.%.
[0025] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0026] Preparation of carrier SBA-15: Weigh 8 g of P123 and 300 mL of 1.6M HCl aqueous solution, stir continuously at 38 °C until they are completely dissolved, add 16 g of tetraethyl orthosilicate (TEOS) under vigorous stirring, stir for another 24 h, transfer to a hydrothermal kettle, and hydroheat at 100 °C for 24 h; then wash alternately with water and ethanol several times, dry at 60 °C overnight, and then calcine at 600 °C in a muffle furnace for 2 h (heating rate 4 °C / min) to obtain an SBA-15 carrier.
[0027] Example 1 1.68 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL deionized water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 12 wt% as measured by ICP.
[0028] Example 2 2.44 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL deionized water, and 3.5 g carrier SBA-15 was added and impregnated for 24 h. Then, it was dried at 60 °C overnight and slightly ground. Then, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in it was about 17 wt% according to ICP measurement.
[0029] Example 3 2.44 g Cu(NO3)2·3H2O and 3.5 g melamine were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0030] Example 4 2.44 g Cu(NO3)2·3H2O and 3.5 g dicyandiamide were dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0031] Example 5 1.62 g CuSO4 and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, the mixture was calcined at 600 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0032] Example 6 1.25 g CuCO3 and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, the mixture was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0033] Example 7 2.44 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 600 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0034] Example 8 3.31 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 22 wt% as measured by ICP.
[0035] Example 9 4.28 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 27 wt% as measured by ICP.
[0036] Example 10 5.40 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 32 wt% as measured by ICP.
[0037] Embodiment 11 2.44 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tubular furnace in a nitrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0038] Example 12 2.44 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g carrier SBA-15 was added. The mixture was allowed to stand for 24 h, then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in an air atmosphere for 1 h (heating rate 4 °C / min) in a tube furnace to obtain a Cu-NC / SBA-15 catalyst precursor. The Cu content in the catalyst was about 17 wt% as measured by ICP.
[0039] Comparative Example 1 2.44 g Cu(NO3)2·3H2O and 3.5 g urea were weighed and dissolved in 12 mL water, and 3.5 g of commercial SiO2 carrier was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, it was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SiO2 catalyst precursor. The Cu content in the precursor was about 17 wt% as measured by ICP.
[0040] Comparative Example 2 2.44 g Cu(NO3)2·3H2O was weighed and dissolved in 12 mL water, and 3.5 g of carrier SBA-15 was added. The mixture was allowed to stand for 24 h and then dried at 60 °C overnight. After slight grinding, the mixture was calcined at 500 °C in a tube furnace in a hydrogen atmosphere for 1 h (heating rate 4 °C / min) to obtain a Cu-NC / SBA-15 catalyst precursor with a Cu content of 17 wt%.
[0041] 0.5 g (40-60 mesh) of the catalyst precursors prepared in the example and the comparative example were weighed respectively, and reduced in a fixed bed reactor (reduction temperature was 350° C., reduction time was 3 h, and reduction atmosphere was 5 vol.% H2 / N2) to obtain a copper-supported catalyst.
[0042] Figure 1The following are the small-angle XRD spectra of the carrier SBA-15 and the catalyst precursor obtained in Example 2. As can be seen from the figure, Example 2 has three obvious diffraction peaks at 1.3°, 2.2° and 2.4°, which are respectively attributed to the (100), (110) and (200) diffraction peaks of the ordered two-dimensional (2D) hexagonal mesostructure SBA-15, indicating that the loading of metal Cu and the modification with g-C3N4 have no significant effect on the symmetry of the mesoporous framework.
[0043] Figure 2 The XRD spectra of the commercial SiO2 carrier, SBA-15 carrier, Example 2 and Comparative Examples 1-2 after reduction at 350°C are shown in the figure. As can be seen from the figure, the peak intensities of Cu and Cu2O in Example 2 are both relatively low, indicating that the Cu and Cu2O grains in the catalyst bulk phase are relatively small and have a high degree of dispersion.
[0044] Figure 3 The H2-TPR graphs of the catalyst precursors obtained in Example 2 and Comparative Examples 1 and 2. As can be seen from the graph, compared with Comparative Examples 1 and 2, the reduction temperature of the catalyst sample obtained in Example 2 is lower, indicating that there is a good synergistic effect between the metal and the carrier.
[0045] Figure 4 The activity comparison diagram of the catalyst precursor obtained in Example 1-12 and Comparative Example 1-2 after reduction at 350°C. Figure 4 As can be seen in a, by comparing with Comparative Examples 1 and 2, the CO conversion rates of the catalyst sample of Example 2 at 200°C, 240°C, 280°C, 320°C and 360°C are 91.0%, 95.0%, 92.2%, 91.8% and 91.4%, respectively. The catalyst sample of Example 2 has higher catalytic activity than that of the comparative example, indicating that the catalyst with SBA-15 as the carrier under the action of the polymer has more advantages; Figure 4 b shows that the optimal Cu loading is 17%. Figure 4 c and Figure 4 It can be seen that different calcination atmospheres, different polymers, different copper salts and different calcination temperatures also have a significant effect on the activity, among which Example 2 has the best CO conversion rate, and the best calcination temperature is 500 °C.
[0046] Figure 5The WGS stability diagram of the catalysts obtained in Example 2 and Comparative Examples 1-2 at 240°C. It can be seen from the figure that in the test lasting up to 50 hours, the CO conversion rate of Example 2 remained relatively stable with almost no loss, while the CO conversion rates of Comparative Examples 1 and 2 both suffered losses to varying degrees, wherein the CO conversion rate of Comparative Example 1 lost about 15% within 50 hours, and the CO conversion rate of Comparative Example 2 lost about 5% within 50 hours. This indicates that the stability of the catalyst can be effectively improved under the action of the polymer using SBA-15 as a carrier.
[0047] Figure 6 TEM images of the catalysts obtained in Example 2 and Comparative Example 2. As can be seen from the figure, the Cu particles with a diameter of 2-6 nm in Example 2 are dispersed in the SBA-15 pores, while the larger particles with a diameter of 4-8 nm in Comparative Example 2 are dispersed on the surface of SBA-15, indicating that the g-C3N4 formed by the polymer anchors Cu to form smaller nanoparticles and fixes them in defect sites, thereby dispersing them in the SBA-15 pores.
[0048] Table 1 is a comparison of the process parameters and structural parameters of the catalyst precursors prepared in the examples and comparative examples.
[0049] Table 1 Process parameters and structural parameters of different catalyst precursors As can be seen from Table 1, by comparing Examples 1-12, Comparative Example 2 and Comparative Example 1, it can be seen that the specific surface area of the catalyst precursor with SBA-15 as a carrier is larger than the specific surface area of the catalyst precursor with SiO2 as a carrier, indicating that SBA-15 as a carrier can significantly increase the specific surface area of the catalyst precursor. Comparative Example 2 and Comparative Example 2 found that the specific surface area and pore volume of the catalyst precursor added with the polymer increased significantly, which is because the Cu particles are dispersed in the pores by limiting their size to provide more specific surface area and molecular diffusion channels. By comparing Examples 1, 2, 8, 9, and 10, it can be seen that the specific surface areas of catalyst precursors with different loadings are different, which is due to the different degrees of metal occupation of the SBA-15 pores, indicating that the metal loading will affect the specific surface area of the catalyst precursor. At the same time, through the comparison of Example 2 with Examples 3 and 4, the comparison of Example 2 with Examples 5 and 6, the comparison of Example 2 with Examples 11 and 12, and the comparison of Example 2 with Example 7, it can be seen that the polymer, copper salt, calcination atmosphere and calcination temperature will also affect the specific surface area and pore volume of the catalyst precursor.
[0050] Catalyst performance evaluation Weigh 0.5 g of each catalyst prepared in the embodiment and the comparative example, respectively, and test the activity under the following conditions: the dry feed gas composition is 15% CO, 55% H2, 7% CO2, 23% N2 (volume fraction); the molar ratio of water vapor to dry feed gas is 1:1; the air velocity is 4500 mL·g -1 ·h -1 The test temperature range is 200~360 ℃. The activity of the catalyst is expressed by CO conversion rate, CO conversion rate = (1-V CO ′ / V CO ) / (1+V CO ′)×100%, where V CO and V CO ' is the volume fraction of CO in the dry feed gas and the outlet gas, respectively. The activity evaluation results of the catalysts obtained in the examples and comparative examples are shown in Table 2.
[0051] Table 2 Activity evaluation results of copper-supported catalysts obtained in Examples and Comparative Examples As shown in the results of Table 2, compared with Comparative Example 1, Examples 1-12 show that compared with the traditional Cu / SiO2 catalyst, the performance of the catalyst with SBA-15 as the carrier is better; the g-C3N4 formed by the addition of the polymer can effectively improve the reaction activity. Compared with Examples 1, 8, 9, and 10, the catalyst prepared in Example 2 shows better performance in the water-gas shift reaction, indicating that the loading amount of Cu has a significant effect on the reaction activity. Further, by comparing the results of Example 2 with Examples 11 and 12, it can be seen that the H2 activation atmosphere is beneficial to improving the activity of the catalyst. This is attributed to the promoting effect of the activation atmosphere on the interaction between the active components and the carrier. Compared with other atmospheres such as N2 and Air, the H2 atmosphere can significantly improve the catalytic activity of the copper-based catalyst in the water-gas shift reaction. It can be seen from Examples 2 and 3, 4, Example 2 and Examples 5, 6, and Example 2 and Example 7 that the selection of polymers, copper salts, and calcination temperatures will affect the performance of the Cu-NC / SBA-15 catalyst in the water-gas shift reaction.
[0052] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a copper-supported catalyst with spatial confinement effect for water-gas shift reaction, characterized in that: The catalyst is prepared by anchoring active component Cu nanoparticles on defect sites of g-C3N4 and confining the active component Cu nanoparticles in the pores of an SBA-15 carrier to obtain a supported Cu-NC / SBA-15 catalyst.
2. The method for preparing a copper-supported catalyst with spatial confinement effect for water-gas shift reaction according to claim 1, characterized in that: The following steps are involved: (1) Preparation of carrier SBA-15: The organic structure directing agent P123 was dissolved in hydrochloric acid, and then the silicon salt precursor was slowly added under vigorous stirring. The mixed solution was stirred for 24 h and then transferred into a stainless steel autoclave for hydrothermal reaction for 24 h. The product was filtered, washed, dried and calcined to obtain SBA-15. (2) Metal loading: The polymer and copper salt are dissolved in deionized water, and the SBA-15 carrier is added for impregnation to obtain a Cu-NC / SBA-15 wet sample; then, the Cu-NC / SBA-15 catalyst precursor is obtained by drying, grinding, and calcining; (3) The Cu-NC / SBA-15 catalyst precursor obtained in step (2) is reduced to obtain a copper-based catalyst.
3. The method for preparing a copper-supported catalyst with confinement effect for water-gas shift reaction according to claim 2, characterized in that: In step (1), the ratio of the organic structure directing agent P123, the silicon salt precursor and the hydrochloric acid is 1 g:2 g:37.5 mL; the silicon salt precursor is tetraethyl orthosilicate.
4. The method for preparing a copper-supported catalyst with confinement effect for water-gas shift reaction according to claim 2, characterized in that: The stirring temperature in step (1) is 35-40°C; the temperature of the hydrothermal reaction is 100-150°C; and the calcination is carried out under static air at a rate of 4-5°C / min to 500-600°C and maintained for 2-3 hours.
5. The method for preparing a copper-supported catalyst with confinement effect for water-gas shift reaction according to claim 2, characterized in that: The copper salt in step (2) includes one or more of copper nitrate, copper carbonate, copper chloride, and copper sulfate; the copper loading in the catalyst is 12-32 wt.%.
6. The method for preparing a copper-supported catalyst with confinement effect for water-gas shift reaction according to claim 2, characterized in that: The polymer described in step (2) includes one or more of melamine, urea, cyanamide, and dicyandiamide, and the mass ratio of the polymer to the carrier SBA-15 is 1:
1.
7. The method for preparing a copper-supported catalyst with confinement effect for water-gas shift reaction according to claim 2, characterized in that: The impregnation time in step (2) is 12-24 h; the calcination condition is to increase the temperature to 500-600 °C at a rate of 4 °C / min under hydrogen, nitrogen or air, and maintain it for 1-2 h.
8. The method for preparing a copper-supported catalyst with spatial confinement effect for water-gas shift reaction according to claim 2, characterized in that: The reduction in step (3) is carried out in an atmosphere of 5 vol.% H2 / N2 at 300-400°C for 2-4 h.
9. A copper-supported catalyst with spatial confinement effect for water-gas shift reaction prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the copper-supported catalyst with spatial confinement effect for water-gas shift reaction as claimed in claim 9 in water-gas shift reaction.
Citation Information
Patent Citations
Method for preparing Cu-based water-gas shift catalyst by using mesoporous silicon as template
CN105107513A
Nitrogen-containing organic liquid hydrogen storage non-noble metal catalyst for fixed bed reactor
CN114768858A
Preparation method of carbon nitride-based copper material for ozone catalytic oxidation water treatment
CN115228503A
Copper-iron supported catalyst for water gas shift reaction and preparation method thereof
CN118059920A
Method for manufacturing carbon nitride porous material (MCN)
JP2010030844A